Impacto de las tecnologías de la información y la comunicación (TICs) en el rendimiento académico durante el proceso de enseñanza-aprendizaje de los alumnos de octavo grado de educación general básica del colegio de bachillerato Juan Montalvo de la ciudad de Machala, periodo lectivo 2012-2013. - Espinoza Suárez, Jinsson Oswaldo (2014)
Today many teachers have limitations on the use of new technologies, a situation that is given by the lack of frequent and updated training, in addition to that which the institution does not have suitable hardware for optimal development of the teaching learning all this unfortunate reality in which they are immersed our educational institutions, negatively affects obtaining bachelors trained effectively and efficiently, which have previously made significant learning in order to guarantee quality performance as a professional.